Comparison of the prevalence of error of refraction and color blindness among private and public primary pupils in Nueva Valencia, Guimaras. - Benitez, Ninotchka Vyent B.; Fuentes, Elyssa Marie C.
Refractive error is the number one cause of childhood blindness in the Philippines with a prevalence rate of 53 percent (3rd National Blindness Survey, 2004). Color blindness is an abnormal condition characterized by the inability to clearly distinguish different colors of the spectrum. This is a descriptive cross-sectional study aimed to assess the visual acuity using the Snellen Chart and prevalence of color blindness using the Ishihara pseudochromatic plates, among private and public elementary school pupils in Nueva Valencia Guimaras. A total of 324 elementary pupils were included, 113 of them belonged to private school and 214 belonging to public school. The prevalence for both error of refraction (83/63) and color blindness (52/60)is significantly higher in private school than in public school. Age is a factor in developing both disorders. There is a direct correlation between higher income, and error of refraction and color blindness. Several factors could attribute to the results, including diagnostic procedures and lifestyle of the pupils. This study should help raise awareness regarding error of refraction and color blindness to the public, most specially to the parents who tend to neglect the visual performance of their children.